Glucose oxidation performance is improved by the use of a supramolecular self-assembly of glucose oxidase and catalase. Issue 2 (2nd January 2019) - Cui, Caixia; Fang, Yunming; Chen, Biqiang; Tan, Tianwei
Abstract : A multi-enzymes complex was assembled successfully via host/guest interactions, and it was used for rapid transformation of glucose. Abstract : The construction and catalytic application of multi-enzymatic systems have attracted much research attention. Herein, we demonstrate an effective approach for the construction of a glucose oxidase (GOX) and catalase (CAT) matrix via the supramolecular recognition of β-cyclodextrin (grafted to GOX) and adamantane (grafted to CAT). This forms a self-assembling multi-enzyme system (SAME) spontaneously after simple mixing. In the SAME, GOX activity and k cat / K m were 3.7 and 7 times greater than in the GOX/CAT mixture. Kinetic analysis indicated that the SAME improved catalysis because hydrogen peroxide was rapidly consumed by the adjacent CAT. Furthermore, the mixture and SAME was used to synthesize gluconic acid from glucose, the GOX/CAT SAME exhibited higher reaction rates than did the GOX/CAT mixtures at the same glucose concentrations; these differences were particularly noticeable at higher substrate glucose concentrations. These results suggest that SAMEs constructed by the method described herein might increase cascade reaction rates and be more suitable for high glucose concentrations.